KARAKTERISTIK TEPUNG KACANG MERAH PREGELATINISASI DENGAN METODE PENGERINGAN OVEN DAN SANGRAI SERTA EFEKNYA PADA TEKSTUR CAKE NON GLUTEN - Anita Maya Sutedja; Ch. Yayuk Trisnawati; Agatha Levina Candra; Margareta Advista Giantiva (JURNAL AGROTEKNOLOGI, 2015)
Kidney beans contain low fat content, and high enough of protein and starch content, so it potential to be utilized. Kidney beans were steamed first before drying process to obtained pregelatinization kidney bean flour. Roast and oven method is evaporation process that generally done by people and they can reduce water content, extend shelf life and easy to use. Application of kidney bean flour as fat replacer in non gluten cake affect the cake texture. The purpose of this research is to determine the effect using oven and roast drying method in characteristics of kidney bean flour and non gluten cake texture. Evaluation of cake texture was done objectively and subjectively with semi trained panelist. The result of four replication showed that oven and roast drying method gave significant difference t-test (α=5%) in water content, water absorption capacity, oil absorption capacity, foam capacity, and emulsion stability, but there was not significant difference in emulsion capacity. It also not gave significant difference t-test (α=5%) in non gluten cake texture included objective (hardness, springiness) and subjective (ease bitten and softness), but gave significant difference in cohesiveness.Keywords: kidney bean flour, pregelatinization, drying, oven, roast